Safety at work - Ridley, John R.; Channing, John. (Amsterdam ; Boston. : Butterworth Heinemann, 2003)
Safety at Work is widely accepted as the authoritative guide to safety and health in the workplace and covers all aspects of safety management. The sixth edition has been revised to cover recent changes to UK practice and standards in health, safety, employment and environmental legislation. It also incorporates EU directives and references to harmonised and international standards. Reflecting the importance of the roles of directors and managers in health and safety, new chapters cover the management of risk, emphasising the need for a sound organisational structure to achieve effective risk management. Developments in the behavioural approach to risk management and current thinking on the development of an international standard on safety management are also covered. Quality of the environment is rapidly becoming part of the safety manager's responsibilities both in the workplace and in the context of global pollution. A completely new part consisting of five chapters has been added dealing solely with environmental issues (including ISO 14001). The increasingly important role of ergonomics in health and safety is reflected in a new chapter on Applied Ergonomics, dealing with the subject pragmatically, that will allow the manager and practitioner to design process and operations that are within the limits of the human body. The effects of stress, an emerging concern in health and safety, are covered in various chapters. * The leading book on the subject of occupational safety that covers all aspects of safety management. * Revised to include changes in health, safety, employment and environmental legislation and issues. * Covers information required for NEBOSH and IOSH qualifications.
Explaining the law -- Principal health and safety Acts -- Influences on health and safety -- Law of contract -- Employment law -- Consumer protection -- Insurance cover and compensation -- Civil liability -- An introduction to risk management -- Principles of the management of risk -- Risk management: organisation and administration for safety -- Risk management: techniques and practices -- The collection and use of accident and incident data -- Practical safety management: systems and techniques -- The individual and safety -- Risk management and behaviour modification -- The structure and functions of the human body -- Occupational diseases -- Occupational hygiene -- Radiation -- Noise and vibration -- Workplace pollution, heat and ventilation -- Lighting -- Managing ergonomics -- Applied ergonomics -- Science in engineering safety -- Fire precautions -- Safe use of machinery -- Electricity -- Statutory examination of plant and equipment -- Safety on construction sites -- Managing chemicals safely -- The environment: issues, concepts and strategies -- Environmental management systems -- Waste management -- Chemicals and the environment -- The environment at large.
Includes bibliographical references and index.
Keywords: Industrial safety; Occupational Diseases -- Prevention and control; Accidents, Occupational -- Prevention & control; Electronic books